The Mapuche public speech: Identity construction and cultural dialogue - Nitrihual Valdebenito, Luis; Fierro Bustos, Juan Manuel; Mayorga Rojel, Alberto Javier (Estudios sobre el Mensaje Periodístico, 2012)
This work reviews the notion of mapuche public discourse as textual complex produced for mass by communities, collective media and groups located mainly in urban areas of Chile. Raises the discussion from Iuri Lotman concepts on text, cultural dialogue and construction of identity in the media. To show how these speeches (re) build an identity entrenched in the recovery of ancestral memory, we reviewed a small corpus of public declarations taken randomly.